Chemical and Morphological Transition of Poly(acrylonitrile)/Poly(vinylidene Fluoride) Blend Nanofibers during Oxidative Stabilization and Incipient Carbonization - Wortmann, Martin; Frese, Natalie; Mamun, Al; Trabelsi, Marah; Keil, Waldemar; Büker, Björn; Javed, Ali; Tiemann, Michael; Moritzer, Elmar; Ehrmann, Andrea; Hütten, Andreas; Schmidt, Claudia; et al. (Nanomaterials)
Thermally stabilized and subsequently carbonized nanofibers are a promising material for many technical applications in fields such as tissue engineering or energy storage. They can be obtained from a variety of different polymer precursors via electrospinning. While some methods have been tested for post-carbonization doping of nanofibers with the desired ingredients, very little is known about carbonization of blend nanofibers from two or more polymeric precursors. In this paper, we report on the preparation, thermal treatment and resulting properties of poly(acrylonitrile) (PAN)/poly(vinylidene fluoride) (PVDF) blend nanofibers produced by wire-based electrospinning of binary polymer solutions. Using a wide variety of spectroscopic, microscopic and thermal characterization methods, the chemical and morphological transition during oxidative stabilization (280 °C) and incipient carbonization (500 °C) was thoroughly investigated. Both PAN and PVDF precursor polymers were detected and analyzed qualitatively and quantitatively during all stages of thermal treatment. Compared to pure PAN nanofibers, the blend nanofibers showed increased fiber diameters, strong reduction of undesired morphological changes during oxidative stabilization and increased conductivity after carbonization.

Humidity-Mediated Anisotropic Proton Conductivity through the 1D Channels of Co-MOF-74 - Javed, Ali; Strauss, Ina; Bunzen, Hana; Caro, Jürgen; Tiemann, Michael (Nanomaterials)
Large Co-MOF-74 crystals of a few hundred micrometers were prepared by solvothermal synthesis, and their structure and morphology were characterized by scanning electron microscopy (SEM), IR, and Raman spectroscopy. The hydrothermal stability of the material up to 60 °C at 93% relative humidity was verified by temperature-dependent XRD. Proton conductivity was studied by impedance spectroscopy, using a single crystal. By varying the relative humidity (70–95%), temperature (21–60 °C), and orientation of the crystal relative to the electrical potential, it was found that proton conduction occurs predominantly through the linear, unidirectional (1D) micropore channels of Co-MOF-74, and that water molecules inside the channels are responsible for the proton mobility by a Grotthuss-type mechanism.

Cellulose Nanocrystal-Templated Tin Dioxide Thin Films for Gas Sensing - Ivanova, Alesja; Frka-Petesic, Bruno; Paul, Andrej; Wagner, Thorsten; Jumabekov, Askhat N.; Vilk, Yury; Weber, Johannes; Schmedt auf der Günne, Jörn; Vignolini, Silvia; Tiemann, Michael; Fattakhova-Rohlfing, Dina; Bein, Thomas (ACS Applied Materials & Interfaces)
Porous tin dioxide is an important low-cost semiconductor applied in electronics, gas sensors, and biosensors. Here, we present a versatile template-assisted synthesis of nanostructured tin dioxide thin films using cellulose nanocrystals (CNCs). We demonstrate that the structural features of CNC-templated tin dioxide films strongly depend on the precursor composition. The precursor properties were studied by using low-temperature nuclear magnetic resonance spectroscopy of tin tetrachloride in solution. We demonstrate that it is possible to optimize the precursor conditions to obtain homogeneous precursor mixtures and therefore highly porous thin films with pore dimensions in the range of 10–20 nm (ABET = 46–64 m2 g–1, measured on powder). Finally, by exploiting the high surface area of the material, we developed a resistive gas sensor based on CNC-templated tin dioxide. The sensor shows high sensitivity to carbon monoxide (CO) in ppm concentrations and low cross-sensitivity to humidity. Most importantly, the sensing kinetics are remarkably fast; both the response to the analyte gas and the signal decay after gas exposure occur within a few seconds, faster than in standard SnO2-based CO sensors. This is attributed to the high gas accessibility of the very thin porous film.

Nanoporous aluminum oxide micropatterns prepared by hydrogel templating - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanotechnology)
Micropatterned nanoporous aluminum oxide arrays are prepared on silicon wafer substrates by using photopolymerized poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel micropatterns are fabricated by spreading the prepolymer mixture on the substrate, followed by UV photopolymerization through a micropatterned mask. The hydrogel is covalently bonded to the substrate surface. Al2O3 is produced by swelling the hydrogel in a saturated aluminum nitrate solution and subsequent thermal conversion/calcination. As a result, micropatterned porous Al2O3 microdots with heights in µm range and large specific surface areas up to 274 m2 g−1 are obtained. Hence, the hydrogel fulfills a dual templating function, namely micropatterning and nanoporosity generation. The impact of varying the photopolymerization time on the properties of the products is studied. Samples are characterized by light and confocal laser scanning microscopy, scanning electron microscopy, energy-dispersive x-ray spectrometry, and Kr physisorption analysis.

Synthesis of Metal Oxide Inverse Opals from Metal Nitrates by PMMA Colloidal Crystal Templating - Zhang, Xuyang; Weinberger, Christian; Amrehn, Sabrina; Wu, Xia; Tiemann, Michael; Wagner, Thorsten (European Journal of Inorganic Chemistry)
Metal oxide inverse opals are interesting for various applications. To achieve highly ordered inverse opal structures, one important issue during the colloidal crystal templating procedure is to form a stable precursor network before the template loses its structural integrity at high temperature. Using poly(methyl methacrylate), PMMA, colloidal crystal templates, it is essential to consider the physical and chemical changes of the precursors induced by the changes of PMMA during the thermal conversion. For a systematic investigation of this matter, we synthesized a variety of metal oxide inverse opals from the respective metal nitrates, including Cr2O3, Ga2O3, Fe2O3, In2O3, CuO, CeO2, and ZnO, to compare the effect of various modifications of precursors on the structural and optical properties. When the nitrate precursors have a lower thermal stability than the PMMA template, we have modified the metal nitrates by chelating or by polyacrylamide gelation to form more stable precursor networks.

Proton Conduction in a Single Crystal of a Phosphonato‐Sulfonate‐Based Coordination Polymer: Mechanistic Insight - Javed, Ali; Wagner, Thorsten; Wöhlbrandt, Stephan; Stock, Norbert; Tiemann, Michael (ChemPhysChem)
The proton conduction properties of a phosphonato-sulfonate-based coordination polymer are studied by impedance spectroscopy using a single crystal specimen. Two distinct conduction mechanisms are identified. Water-mediated conductance along the crystal surface occurs by mass transport, as evidenced by a high activation energy (0.54 eV). In addition, intrinsic conduction by proton ′hopping′ through the interior of the crystal with a low activation energy (0.31 eV) is observed. This latter conduction is anisotropic with respect to the crystal structure and seems to occur through a channel along the c axis of the orthorhombic crystal. Proton conduction is assumed to be mediated by sulfonate groups and non-coordinating water molecules that are part of the crystal structure.

Functional Nanoporous Materials - Weinberger, Christian; Tiemann, Michael (Nanomaterials)
This Special Issue on “Functional Nanoporous Materials” in the MDPI journal nanomaterials features seven original papers ...

Long- and Short-Term Tensile Strength and Morphology of Joined Beta-Nucleated Polypropylene Parts - Wübbeke, Andrea; Schöppner, Volker; Paul, André; Tiemann, Michael; Austermeier, Laura; Fitze, Marcus; Chen, Mingie; Jakob, Fabian; Heim, Hans-Peter; Wu, Tao; Niendorf, Thomas; Röhricht, Marie-Luise; et al. (SPE ANTEC 2020: The Virtual Edition 5)
This paper presents the results of static short-term and long-term tensile tests for beta-nucleated joined polypropylene samples by the hot plate welding process. In the present study different dimensionless joining displacements are accounted for. The results show that high short-term tensile strength does not directly transfer to high long-term tensile strength. The morphology of the weld seam in the joined samples is examined by means of transmitted and reflected light microscopy. For the dimensionless joining displacements of 0.75 and 0.95, stretched spherulites are obtained. X-Ray diffraction can be used as a tool for qualitative and quantitative analysis and eventually for differentiation of samples of various joining displacements.

Selected Aspects for the Assessment of Laser Transmission Welding - Schöppner, Volker; Wübbeke, Andrea; Schriegel, Fabian; Paul, Andrej; Tiemann, Michael; Geißler, Bastian; Schmidt, Michael; Magnier, Arnaud; Niendorf, Thomas (Joining Plastics)
In diesem Artikel werden das Scherzugverhalten und der morphologische Zustand von konturgeschweißtem Polypropylen (PP) mit einem Massenanteil von 0,2% Ruß untersucht. Dabei zeigen die Ergebnisse ...

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Janus-type dual emission of a Cyclometalated Iron(III) complex - Bauer, Matthias; Steube, Jakob; Päpcke, Ayla; Bokareva, Olga; Reuter, Thomas; Demeshko, Serhiy; Schoch, Roland; Hohloch, Stephan; Meyer, Franc; Heinze, Katja; Kühn, Oliver; Lochbrunner, Stefan
Photoactive compounds are essential for photocatalytic and luminescent applications, such as photoredox catalysis or light emitting diodes. However, the substitution of noble metals, which are almost exclusively used, by base metals remains a major challenge on the way to a more sustainable world.1 Iron is a dream candidate for this ambitious aim.2 But compared to noble metal complexes that show long-lived metal-to-ligand charge-transfer (MLCT) states, realization of emissive and photoactive iron complexes is demanding, due to the fast deactivation of charge transfer states into non-emissive inactive states. No MLCT emission has been observed for monometallic iron complexes before. Consequently, dual emission could also not yet be realized with iron complexes, as it is a very rare property even of noble metal compounds. Here we report the Fe III complex [Fe(ImP) 2 ][PF 6 ] (HImP = 1,1’-(1,3-phenylene)bis(3-methyl-1-imidazol-2-ylidene)), showing Janus-type dual emission by combining LMCT (ligand-to-metal charge transfer) with MLCT luminescence. The respective excited states are characterized by a record lifetime of τ MLCT = 4.2 ns, and a moderate τ LMCT = 0.2 ns. Only two emissive Fe III compounds are known so far and they show LMCT luminescence only.3,4 The unique properties of the presented complex are caused by the specific ligand design combining four N-heterocyclic carbenes with two cyclometalating groups, using the σ-donor strength of six carbon atoms and the acceptor capabilities of the central phenyl rings. Spectroscopically, doublet manifolds could be identified in the deactivation process, while (TD)DFT analysis revealed the presence of quartets as well. With three key advancements of realizing the first iron complex showing dual luminescence, a MLCT luminescence and a world record MLCT lifetime, the results constitute a basis for future application of iron complexes as white light emitters and new photocatalytic reactions making use of the Janus-type properties of the developed complex.

Experimental and Theoretical Study on the Role of Monomeric vs Dimeric Rhodium Oxazolidinone Norbornadiene Complexes in Catalytic Asymmetric 1,2- and 1,4-Additions - Kirchhof, Manuel; Gugeler, Katrin; Fischer, Felix Richard; Nowakowski, Michał; Bauer, Alina; Alvarez-Barcia, Sonia; Abitaev, Karina; Schnierle, Marc; Qawasmi, Yaseen; Frey, Wolfgang; Baro, Angelika; Estes, Deven P.; et al. (Organometallics)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Charge Distribution in Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes: A Combined X-ray, XAS, XES, DFT, Mössbauer, and Catalysis Approach - Benedikter, Mathis; Musso, Janis; Kesharwani, Manoj K.; Sterz, K. Leonard; Elser, Iris; Ziegler, Felix; Fischer, Felix; Plietker, Bernd; Frey, Wolfgang; Kästner, Johannes; Winkler, Mario; van Slageren, Joris; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Stereoselective Chromium‐Catalyzed Semi‐Hydrogenation of Alkynes - Gregori, Bernhard J.; Nowakowski, Michał; Schoch, Anke; Pöllath, Simon; Zweck, Josef; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Electronic Structure of the Hieber Anion [Fe(CO)3(NO)]− Revisited by X-ray Emission and Absorption Spectroscopy - Burkhardt, Lukas; Vukadinovic, Yannik; Nowakowski, Michał; Kalinko, Aleksandr; Rudolph, Julian; Carlsson, Per-Anders; Jacob, Christoph R.; Bauer, Matthias (Inorganic Chemistry)

Impact of Al Activators on Structure and Catalytic Performance of Cr Catalysts in Homogeneous Ethylene Oligomerization – A Multitechnique in situ/operando Study - Grauke, Reni; Schepper, Rahel; Rabeah, Jabor; Schoch, Roland; Bentrup, Ursula; Bauer, Matthias; Brückner, Angelika (ChemCatChem)

Gold(II) Porphyrins in Photoinduced Electron Transfer Reactions - Preiß, Sebastian; Päpcke, Ayla; Burkhardt, Lukas; Großmann, Luca; Lochbrunner, Stefan; Bauer, Matthias; Opatz, Till; Heinze, Katja (Chemistry – A European Journal)

Experimental and Theoretical High Energy Resolution Hard X-ray Absorption and Emission Spectroscopy on Biomimetic Cu2S2 Complexes - Müller, Patrick; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald; Kühne, Thomas D.; Bauer, Matthias (The Journal of Physical Chemistry A)

Probing Iron-Ligand interactions by combining modern high-resolution hard X-ray spectroscopy and density functional theory : a powerful methodology in cases where conventional methods fail / vorgelegt von Lukas Burkhardt ; [Prof. Dr. Matthias Bauer (Erstgutachter), Prof. Dr. Thomas Kühne (Zweitgutachter), Jun. Prof. Dr. Stephan Hohloch (Drittprüfer)] - Burkhardt, Lukas

Experimental and theoretical (high energy resolution) X-ray absorption and emission spectroscopy / vorgelegt von Patrick Müller ; [Promotionskommission: Prof. Dr.-Ing. Hans-Joachim Warnecke, Vorsitz; Prof. Dr. Matthias Bauer, Erstgutachter; Prof. Dr. Thomas D. Kühne, Zweitgutachter; Prof. Dr. Wolf Gero Schmidt] - Müller, Patrick